Prevalence of Diseases in Kallupurwa (Kursi) Area of Barabanki (UP) Lucknow (AYUSHDHARA, 2022)
The village Kallupurwa (Kursi) is a village in district Barabanki, very closed to Lucknow the capital of Uttar Pradesh., where scheduled caste population dominate upper caste and Muslims. The village is more backward than expected and lack health facilities, education and employment. Due to these circumstances people fall prey to all types of infections and most people suffer from malnutrition and other complications. The Scheduled Cast Sub Plan (SCSP) and Tribal Sub Plan (TSP) program was initiated on the recommendation of Honorable Prime Minister of India, Shri Narendra Modi Ji, all over the country by the Ministry of AYUSH and Central Research Institute of Unani Medicine, Lucknow selected this village in 2019 and the mobile clinic programme began its function in the same year under the SCSP project. The work is still going on and the population of this village is receiving Unani Medical treatment for ailments like Arthritis, SualHadm, WajaulBadan, WajaulBatan, Bawaseer, skin allergy and other Non-Communical Disease (NCD) problems. The observation shows that people are satisfied with the SCSP project and demand to CCRUM to continue the project as long as possible.